Hydrogeological map of Italy: the preliminary Sheet N. 348 Antrodoco (Central Italy) - Marco Amanti; Giovanni Conte; Lucio Martarelli; Gennaro Maria Monti; Guido Motteran; Anna Rosa Scalise; Roberto Serafini; Angelantonio Silvi (Acque Sotterranee, 2016)
The Geological Survey of Italy, Italian National Institute for Environmental Protection and Research is realizing the Sheet N.348 Antrodoco (Central Italy) of the Hydrogeological map of Italy as a cartographical test of the Italian hydrogeological survey and mapping guidelines, in the frame of the Italian Geological Cartography Project. The study area is characterized by structural units deeply involved in the Apennine Orogeny (Latium and Abruzzi region territory, Rieti and L’Aquila provinces) and including deposits of marine carbonate shelf, slope, basin and foredeep environments hosting relatively large amounts of groundwater resources. The map was realized to obtain the best possible representation of all hydrogeological elements deriving from field surveys, in order to characterize the hydrogeological asset. A control network for monthly measurement of surface and groundwater flow rates and hydrogeochemical parameters was performed. Data were uploaded in a geographic information system to perform the present preliminary hydrogeological cartography consisting in a main map showing the following hydrogeological complexes based on relative permeability degree (from bottom to top): i) calcareous (Jurassic-Cretaceous; high permeability); ii) calcareous-marly (Upper Cretaceous-Middle Eocene; intermediate permeability); iii) marly-calcareous and marly (Upper Eocene- Upper Miocene; low permeability); iv) flysch (Upper Miocene; low permeability); v) conglomeratic-sandy and detritic (Upper Pliocene- Pleistocene; intermediate permeability); vi) alluvial (Quaternary; low permeability). Among other elements shown in the main map there are hydrographical basin and sub-basin boundaries, stream gauging stations, meteo-climatic stations, streamwater-groundwater exchange processes, hydrostructure boundaries, point and linear spring flow rates, groundwater flow directions. Furthermore, complementary smaller-scale sketches at the margin of the main map were realized (e.g., hydrogeological structure map, hydrogeological complex map based on effective infiltration information, hydrogeological crosssections).